Comment on Ostrom and Cox paper: "Moving beyond panaceas: a multitiered diagnostic approach for social-ecological analysis" - looking beyond the right institutional fit - Clement, Floriane (2011)
Ostrom and Cox review why panacea problems have dominated and misguided natural resource management policies. They propose a framework researchers can use as a diagnostic approach to study social-ecological systems (SES). More than a methodological tool, the SES framework also aims at offering a common language to bridge the disciplinary divide between natural and social sciences. Based on literature review and personal experience, I argue that the features of the framework adequately address the panacea trap to some extent and notably facilitate large N comparative research, as testify newly gained insights into the role of property rights for sustainable forest management. However, the framework could benefit from critical discourse analysis and a more politicised approach to institutional design. First, power and discourses have been neglected as causal conditions. Yet these variables can play a substantial role by influencing actors' behaviour and by shaping, legitimising and giving meaning to institutions. Second, because institutional design largely depends on how socialecological problems are framed, it is important that a common language does not close debates but recognises the multiple perceptions of the reality and the distinct meanings a single term might convey. Lastly, panaceas do not necessarily result from poor science but also often respond to political and economic interests, which are only distantly considered in the framework. Overcoming panaceas therefore requires researchers to engage with other stakeholders in an argumentative space that has fair and inclusive rules for policy deliberation. To conclude, finding the right 'institutional fit' is desirable but might not be sufficient. Ostrom and Cox review the history of panacea problems, defined as 'overly simplified institutional prescriptions' (p.1), in environmental management and conservation. They highlight three major reasons why panaceas have persisted in the history of natural resource management: one is the disciplinary divide between social and natural scientists; the second is the limited set of methods used by social scientists; lastly, scientists have often narrowly focused on a single scale and level of analysis. Those limitations have contributed to partial and flawed understandings of complex social-ecological systems (SES) and ultimately resulted in simplified and inaccurate theories and models. Ostrom and Cox propose an analytical framework to provide a common language across disciplines and support a fine and rigorous analysis of how the interactions of a variety of factors affect outcomes at multiple levels. Their SES framework includes a set of first-tier variables which are sufficiently broad for the framework to be applied to a wide variety of contexts. Those variables are decomposable into sub-variables, thereby offering high analytical clarity and precision. Grounded on almost two decades of observations and findings collected from case studies, lab experiments and games in different settings, it is a remarkable endeavour to capture and categorise the complexity and diversity of human-environment interactions. Furthermore, it offers an appropriate tool to conduct large-N comparative studies. In this respect, the IFRI initiative2 has offered important lessons with implications for policy-making. For instance, the type of property rights alone appears not to make a real difference in the protection of forest resources.